Freedom Imagined: Morality and Aesthetics in Open Source Software Design. - Leach, James; Nafus, Dawn; Krieger, Bernhard (Ethnos: Journal of Anthropology, 2009)
This paper is about the interaction between the human imagination and technology among a self-described 'community': that of developers of Free or Open Source Software. I argue that the moral imagination observable in this phenomenon can be understood with reference to its emergence around specific methods of technical production. Principles of openness, truth, freedom and progress, which are also understood as central to the technical production of good software, are reinforced (as a ethical orientation) by their contribution to making 'good' software. A reciprocal dynamic ensues in which better software is seen as dependent on particular social practices and ideologies while these practices and ideologies are given salience by their success in fostering valuable production. Processes key to the generation of this social form are examined before a number of key features of the practice of programming, such as its often combative and individualistic character, and an absence of women in developer communities, are considered in the light of the analysis.